2018
DOI: 10.17765/2176-9168.2018v11n1p185-201
|View full text |Cite
|
Sign up to set email alerts
|

Lodo De Estação De Tratamento De Esgoto Como Fertilizante No Cultivo De Fumo E Aveia

Abstract: Este artigo teve como objetivo estudar a valorização de lodo de uma Estação de Tratamento de Esgoto (ETE) como fertilizante no cultivo de fumo e aveia. Foram realizados três tratamentos para cada cultura, sendo que o primeiro não utilizou fertilizante, o segundo utilizou como fertilizante o lodo de ETE e o terceiro recebeu adubo mineral. Foram acompanhados nas culturas parâmetros como desenvolvimento das plantas, aspectos sanitários, aspectos nutricionais e presença de metais. Os resultados demonstraram-se pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
3

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 5 publications
0
3
0
3
Order By: Relevance
“…The emergency values and first emergency count as a function of the treated treatment method were shown in Table 2. It was found that the procedures soil + residue at a dose of 10.0 g/dm 3 and soil + residue at a dose of 15.0 g/dm 3 differed statistically in relation to the absolute control and PK cultivation. Regarding the nutrients, it is observed that there is no dry sludge in the ratio C/N has a value close to 13, demonstrating its higher potential as a nitrogen source, although this better performance may not occur in high percentages of the residue, which was observed in this work.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…The emergency values and first emergency count as a function of the treated treatment method were shown in Table 2. It was found that the procedures soil + residue at a dose of 10.0 g/dm 3 and soil + residue at a dose of 15.0 g/dm 3 differed statistically in relation to the absolute control and PK cultivation. Regarding the nutrients, it is observed that there is no dry sludge in the ratio C/N has a value close to 13, demonstrating its higher potential as a nitrogen source, although this better performance may not occur in high percentages of the residue, which was observed in this work.…”
Section: Resultsmentioning
confidence: 96%
“…For the type and condition of the substrate used within a 45-day study period or the method of promoting an increase in recovering soil quality, this value is not respected by the significant increase in key technical characteristics such as phosphorus, or potassium, or magnesium, an organic matter and CTC [10]. .0 g/dm 3 14* 10* 9* 5* 20.0 g/dm 3 3 NS 2 NS -2 NS -3 NS 25.0 g/dm Soil + residue treatment at 15.0 g/dm 3 is the longest shoot and root length, being significant for the absolute control and for PK cultivation (Table 4). Nutrient contents contained in sewage sludge were used for plant growth due to the amount of nitrogen, as N is one of the elements that directly participates in protein reproduction and consequently in cell expansion and formation of indispensable new tissues.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Além disso, pode gerar um aumento da produtividade das culturas e redução do uso de fertilizantes minerais, contribuindo para a conservação ambiental pela efetivação de métodos adequados e mais econômicos de disposição final desse resíduo. No P a g e | 50 Revista Ibero-Americana de Ciências Ambientais v.12 -n.1  Jan 2021 entanto, para que os solos possam receber aplicação de adubo proveniente de lodo de esgotos, devem obedecer à legislação vigente, e respeitar a proximidade de áreas residenciais, a direção predominante de ventos e a declividade mínima da área (TSUTIYA, 2001). Emergência de plântula de feijão-de corda com o adubo obtido Durante os 15 dias dos tratamentos, foram obtidas 3 plântulas (3%) emergidas no tratamento do solo sem adubação.…”
Section: Obtenção Do Adubounclassified
“…Partindo deste princípio, algumas pesquisas apontaram o uso do lodo de esgoto com perspectivas favoráveis para a produção de mudas florestais (Delarmelina et al 2014;Gomes et al 2013;Rocha et al 2013). Um dos aspectos mais promissores da utilização deste insumo para a composição de substratos, está no fato dele ser fonte de matéria orgânica (MO), carbono orgânico (C org), nitrogênio (N), fósforo (P), potássio (K), cálcio (Ca) e magnésio (Mg) como macronutrientes, além do cobre (Cu), zinco (Zn) e manganês (Mn), como micronutrientes (Zomer et al 2018). Em relação a esses elementos, parte deles é liberada gradativamente e atuarão de forma direta no desenvolvimento das mudas durante todo o ciclo de produção, de modo a suprir as necessidades nutricionais existentes (Bonini et al 2015).…”
Section: Introductionunclassified